Pharmacokinetics of lopinavir/ritonavir oral solution to treat COVID-19 in mechanically ventilated ICU patients. (20th July 2020) - Lê, Minh Patrick; Jaquet, Pierre; Patrier, Juliette; Wicky, Paul-Henri; Le Hingrat, Quentin; Veyrier, Marc; Kauv, Juliette; Sonneville, Romain; Visseaux, Benoit; Laouénan, Cédric; Bouadma, Lila; Descamps, Diane; et al.
Abstract: Background: The combination lopinavir/ritonavir is recommended to treat HIV-infected patients at the dose regimen of 400/100 mg q12h, oral route. The usual lopinavir trough plasma concentrations are 3000–8000 ng/mL. A trend towards a 28 day mortality reduction was observed in COVID-19-infected patients treated with lopinavir/ritonavir. Objectives: To assess the plasma concentrations of lopinavir and ritonavir in patients with severe COVID-19 infection and receiving lopinavir/ritonavir. Patients and methods: Mechanically ventilated patients with COVID-19 infection included in the French COVID-19 cohort and treated with lopinavir/ritonavir were included. Lopinavir/ritonavir combination was administered using the usual adult HIV dose regimen (400/100 mg q12h, oral solution through a nasogastric tube). A half-dose reduction to 400/100 mg q24h was proposed if lopinavir C trough was >8000 ng/mL, the upper limit considered as toxic and reported in HIV-infected patients. Lopinavir and ritonavir pharmacokinetic parameters were determined after an intensive pharmacokinetic analysis. Biological markers of inflammation and liver/kidney function were monitored. Results: Plasma concentrations of lopinavir and ritonavir were first assessed in eight patients treated with lopinavir/ritonavir. Median (IQR) lopinavir C trough reached 27 908 ng/mL (15 928–32 627). After the dose reduction to 400/100 mg q24h, lopinavir/ritonavir pharmacokinetic parameters were assessed in nine patients. Lopinavir C trough decreased to 22 974 ng/mL (21 394–32 735). Conclusions: In mechanically ventilated patients with severe COVID-19 infections, the oral administration of lopinavir/ritonavir elicited plasma exposure of lopinavir more than 6-fold the upper usual expected range. However, it remains difficult to safely recommend its dose reduction without compromising the benefit of the antiviral strategy, and careful pharmacokinetic and toxicity monitoring are needed.